Sugarcane streak mosaic virus (ScSMV) Resistance Evaluation of Sugarcane Varieties - Ernawati, Feny; Djauhari, Syamsuddin; Martosudiro, Mintarto; Putra, Lilik Koesmihartono; Kristini, Ari (Universitas Gadjah Mada, 2022)
Sugarcane streak mosaic virus (ScSMV) is the most important viral disease of sugarcane in Indonesia with distribution in almost all commercial sugarcane plantations. The disease causes significant yield losses of both cane tonnage and sugar yield. The use of resistant varieties is the best approach for controlling viral diseases. This study aims to investigate resistance response of several introduced varieties against ScSMV in a glasshouse condition and the impact of the viral infection on chlorophyll and proline content in sugarcane leaves. Sugarcane plants were inoculated using ScSMV inoculum one month after planting using an abrasive pad rubbing method. Disease incidence and severity was observed at week 4-12 after inoculation and variety resistance levels were classified based on disease incidence. Confirmation of the virus was done by RT-PCR. Spectrophotometer was used to measure chlorophyll content at dual wavelengths of 645 and 663 nm, and proline content at wavelengths of 520 nm. The results showed that most of the tested varieties were susceptible to ScSMV. There are six highly resistant varieties, namely SRA 1, SRA 2, N 10-4, N 10-7, N10-9, and N 10-13, but these varieties still require to be tested on a field scale. ScSMV infection generally decrease chlorophyll and proline content. However, the physiological effect of ScSMV infection on chlorophyll and proline content needs further investigation.